An ecological association of number of civil servants and physicians with prefectural-level rapid COVID-19 vaccination of older people in Japan - Kimiko Tomioka; Midori Shima; Keigo Saeki (Komiyama Printing Co. Ltd, 2023)
Background: Civil servants and physicians play an important role in combating COVID-19. However, it is unclear whether the number of civil servants and physicians is associated with rapid COVID-19 vaccine uptake among older people (i.e., smoother rollout of priority vaccination for older people). Methods: Using Poisson regression models of the generalized estimating equations, we examined the ecological association of the number of civil servants and physicians with prefectural-level rapid COVID-19 vaccination in older people. Prefectural-level data were based on publicly available government surveys. The outcome variable was the proportion of fully vaccinated people aged 65 and older on the day with the largest standard deviation across 47 prefectures (i.e., July 6, 2021). The explanatory variable was the number of civil servants and physicians per population by prefecture. Results: After adjusting for population density, influenza vaccination coverage, socioeconomic factors, natural environmental factors, health indicators, and the number of civil servants and physicians, in all 3 models, prefectures with the highest number of civil servants and physicians had faster COVID-19 vaccine uptake than prefectures with the lowest number. A significant trend between higher staffing levels and more rapid vaccination was observed for the number of physicians in all 3 models, but for the number of civil servants only in one model. Conclusion: We found that COVID-19 vaccine uptake among older people was more rapid in prefectures with more civil servants and physicians per population, with the number of physicians having a stronger association. This study may point the way to future areas of research on vaccine policies that include other age groups and infectious diseases.